2023
DOI: 10.3390/v15010238
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Protective Efficacy of Toll-Like Receptor Ligands to Minimize H9N2 Avian Influenza Virus Transmission in Chickens

Abstract: Low-pathogenicity avian influenza viruses (AIV) of the H9N2 subtype can infect and cause disease in chickens. Little is known about the efficacy of immune-based strategies for reducing the transmission of these viruses. The present study investigated the efficacy of Toll-like receptor (TLR) ligands (CpG ODN 2007 and poly(I:C)) to reduce H9N2 AIV transmission from TLR-treated seeder (trial 1) or inoculated chickens (trial 2) to naive chickens. The results from trial 1 revealed that a low dose of CpG ODN 2007 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have demonstrated that following infections with highly pathogenic AIV, there is a significant increase in the expression of TLR3 and IFN-β in the pulmonary and cerebral tissues of chicks. This points to the central role of TLR3 in mediating the immune defenses against avian influenza ( Raj et al, 2023 ). As a critical pattern recognition receptor, TLR3 is adept at identifying viral RNA, triggering a cascade of signaling mechanisms upon activation.…”
Section: Introductionmentioning
confidence: 91%
“…Recent studies have demonstrated that following infections with highly pathogenic AIV, there is a significant increase in the expression of TLR3 and IFN-β in the pulmonary and cerebral tissues of chicks. This points to the central role of TLR3 in mediating the immune defenses against avian influenza ( Raj et al, 2023 ). As a critical pattern recognition receptor, TLR3 is adept at identifying viral RNA, triggering a cascade of signaling mechanisms upon activation.…”
Section: Introductionmentioning
confidence: 91%
“…The control groups received 100 µL PBS (PBS+ unchallenged and PBS+ challenged). The doses for the ligands used for the present study were determined from our previous studies [29,37].…”
Section: Model B: Experimentally Spiked Fecesmentioning
confidence: 99%
“…Toll‐like receptors (TLRs) are major components of innate immune system in vertebrate species, and these transmembrane proteins are responsible for microbial recognition. Once activated by specific ligands such as bacterial lipopolysaccharide (LPS), glycolipids, viral nucleic acids and CpG Oligodeoxynucleotides (CpG ODN), TLR signals can lead to the recruitment of various immune cells and generate a wide range of biologically active molecules including chemokines, cytokines and antimicrobial peptides, which stimulates the innate immune responses necessary for parasite clearance and resistance to re‐infection 12 …”
Section: Introductionmentioning
confidence: 99%
“…Once activated by specific ligands such as bacterial lipopolysaccharide (LPS), glycolipids, viral nucleic acids and CpG Oligodeoxynucleotides (CpG ODN), TLR signals can lead to the recruitment of various immune cells and generate a wide range of biologically active molecules including chemokines, cytokines and antimicrobial peptides, which stimulates the innate immune responses necessary for parasite clearance and resistance to re-infection. 12 Ten chicken TLRs (chTLRs) are expressed in different host tissues, among which chTLR4 is highly expressed in most tissues and primarily activates the NF-κB signal pathway to kill pathogens. 13,14 chTLR21 shares a high sequence identity with mammalian chTLR9 and is involved in recognition of microbial DNA as a ligand, which triggers immediate innate immune responses and induces adaptive immunity.…”
mentioning
confidence: 99%